The Effect of QRIS Implementation in Digital Banking Service on Bank Probality Indonesia - Ahmad Kamal Assarif; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Research objectives for determine the effect of Qris implementation on Digital Banking services on banking profitability in Indonesia, taking into account BOPO, M-Banking, and Fee Based Income as independent variables. The method used is panel data regression with secondary data obtained from bank annual reports during the 2020-2023 period and BI statistical data. This study found that the variables Qris, BOPO, M-Banking have a negative and significant influence on bank profitability. Meanwhile, the fee-based income variable has a positive but insignificant effect on bank profitability. However, when tested together, the variables Qris, BOPO, M-Banking. Fee Based Income has a positive and significant influence on bank profitability (ROA).